2021
DOI: 10.20892/j.issn.2095-3941.2020.0463
|View full text |Cite
|
Sign up to set email alerts
|

Anlotinib has good efficacy and low toxicity: a phase II study of anlotinib in pre-treated HER-2 negative metastatic breast cancer

Abstract: Objective: Anlotinib is a novel tyrosine kinase inhibitor blocking angiogenesis. This study was performed to assess the efficacy and safety of anlotinib in patients with metastatic breast cancer. Methods: Patients with HER2-negative breast cancer, who were pre-treated with anthracycline or taxanes in a neoadjuvant, adjuvant, or metastatic setting, and had treatment failure after at least one prior chemotherapy regimen in the metastatic setting were enrolled. Anlotinib was administered at 12 mg daily for 14 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 37 publications
4
22
1
Order By: Relevance
“…A previous basic study showed that anlotinib inhibits the proliferation and induces apoptosis of MCF‐7 breast cancer cells by downregulating TFAP2C ( 28 ). At present, only one phase II clinical study with a small sample size has evaluated the clinical efficacy of anlotinib in metastatic breast cancer ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous basic study showed that anlotinib inhibits the proliferation and induces apoptosis of MCF‐7 breast cancer cells by downregulating TFAP2C ( 28 ). At present, only one phase II clinical study with a small sample size has evaluated the clinical efficacy of anlotinib in metastatic breast cancer ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, severe adverse events (AEs, ≥G3) were hypertension (26.92%) and hand–foot syndrome (3.85%). These results showed that anlotinib had good efficacy and limited toxicity with HER2-negative breast cancer ( 26 ). Only one case of advanced MBC treated with anlotinib has been reported.…”
Section: Discussionmentioning
confidence: 96%
“…Anlotinib has been approved by the Chinese Food and Drug Administration for third-line treatment for advanced NSCLC patients. Also, anlotinib has exhibited inspiring efficacy as well as low toxicity in heavily pre-treated HER2-negative metastatic breast cancer ( 21 ).…”
Section: Discussionmentioning
confidence: 99%